2000
DOI: 10.1238/physica.regular.062a00051
|View full text |Cite
|
Sign up to set email alerts
|

Whistlers in Thermally Generated Ducts with Enhanced Plasma Density: Excitation and Propagation

Abstract: A study is made of the excitation and guided propagation of whistler waves along magnetic-field-aligned cylindrical ducts with enhanced plasma density. The ducts have been created in the large plasma device as a result of the thermal-diffusion-driven redistribution of plasma due to electron heating in the quasistatic field of a current loop having a radius commensurate with the electron heat-conduction length in the radial direction. The whistler waves are excited by a comparatively small magnetic loop antenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 25 publications
1
75
0
Order By: Relevance
“…Solid-state plasmas also relied on external wave excitation and detection. But over time large diameter discharge plasmas were developed [57][58][59][60] which nearly eliminated the boundary effects. Nevertheless, plane waves cannot be excited with simple dipole antennas so that a comparison with prevailing theories was not rigorously justified.…”
Section: Whistler Modes In Laboratory Plasmasmentioning
confidence: 99%
“…Solid-state plasmas also relied on external wave excitation and detection. But over time large diameter discharge plasmas were developed [57][58][59][60] which nearly eliminated the boundary effects. Nevertheless, plane waves cannot be excited with simple dipole antennas so that a comparison with prevailing theories was not rigorously justified.…”
Section: Whistler Modes In Laboratory Plasmasmentioning
confidence: 99%
“…Most of the theoretical papers on the subject consider the antennas located in a homogeneous magnetoplasma (see, e. g., [5][6][7][8]). Recently, increased attention has been paid to the study of antenna characteristics in inhomogeneous plasma media [4,[9][10][11]. The case where the antenna is located near the interface of two media (in particular, isotropic and magnetized) is of the greatest interest since the presence of such an interface can significantly affect the current distribution and power characteristics of the sources.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of attention has particularly been devoted to whistler wave excitation in laboratory and space plasmas containing magnetic-fieldaligned density irregularities. [10][11][12][13][14][15][16][17][18][19][20][21][22] Such irregularities, commonly known as density ducts, can exist in the Earth's magnetosphere, in which they ensure guidance of whistler-mode waves naturally occurring under space plasma conditions. 25 Of no less interest are artificial density ducts that can arise due to various nonlinear effects near electromagnetic sources in laboratory and space plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…A number of important features of whistler wave radiation from monochromatic sources in the presence of density ducts have been documented in Refs. [10][11][12][13][14][15][16][17][18][19][20]. In particular, it has been demonstrated that under certain conditions, the presence of a duct can significantly improve the antenna coupling into whistler-mode waves.…”
Section: Introductionmentioning
confidence: 99%